THE CONTENT, FORMATION AND DEVELOPMENT OF MILITARY PEDAGOGICAL CULTURE (American Journal of Interdisciplinary Research and Development, 2024)
The objectives and functions of the article in the learning process, the pedagogical culture of the military, are a complex structure and context, and its formation and improvement are a long-term, continuous, a number of tools and methods.